Private companies and the Companies Act, 1956 : as amended up-to-date - Ghosh, Kshetra Mohan; Palit, Sudhindra Kumar; India; India (Calcutta : Eastern Law House, 1962)
"This work gives ... all the necessary legal provisions and information in regard to the formation and working of Private Companies in India"--Pref.
Includes index and tables.
Keywords: Private companies -- India; Corporation law -- India